Novel Aeromonas hydrophila subsp. inisa with potential phage-mediated tolerance to benzalkonium chloride - Chacon, Luz; Mendoza-Guido, Bradd; Rodríguez-Rojas, Alexandro; Rojas-Jimenez, Keilor (Frontiers in Bacteriology, 2025)
Wastewater treatment plants (WWTPs) serve as hotspots for the proliferation and evolution of specialized microorganisms. Among these, Aeromonas hydrophila stands out as a bacterium capable of colonizing diverse aquatic ecosystems. Its resistance to disinfectants, such as benzalkonium chloride (BAC), is particularly concerning in wastewater treatment systems, where such traits can be propagated. Here, we present a genomic characterization of three isolates belonging to a newly identified subspecies, A. hydrophila subsp. inisa, based on comprehensive genomic analyses. These isolates exhibited higher levels of BAC resistance compared to the reference strain ATCC 7966/DSM 3017 (EC50–27 mg/L vs. 24 mg/L) and contained several prophage sequences integrated into their genomes. These prophages were associated with genetic rearrangements, which may underline phenotypic changes, such as increased antimicrobial resistance. Notably, A. hydrophila subsp. inisa 10 exhibited greater genetic rearrangements and resistance to multiple antibiotics, traits not observed in the other isolates. This study provides the first description of a phage-associated A. hydrophila subspecies isolated from a wastewater system in Central America, underscoring the role of bacteriophages in driving bacterial evolution, speciation, and adaptation to highly polluted environments, such as WWTPs.